A metagenome-wide association study of HIV disease progression in HIV controllers. - Real-Navarrete, Luis Miguel; Saéz, María E; Corma-Gómez, Anaïs; González-Pérez, Antonio; Thorball, Christian; Ruiz, Rocío; Jiménez-León, María Reyes; González-Serna, Alejandro; Gasca-Capote, Carmen; Bravo-Romero, María José; Royo-Sánchez-Palencia, José Luis; Pérez-Gómez, Alberto; et al. (Elsevier, 2023)
Some HIV controllers experience immunologic progression with CD4+ T cell decline. We aimed to identify genetic factors associated with CD4+ T cell lost in HIV controllers. A total of 561 HIV controllers were included, 442 and 119 from the International HIV controllers Study Cohort and the Swiss HIV Cohort Study, respectively. No SNP or gene was associated with the long-term non-progressor HIV spontaneous control phenotype in the individual GWAS or in the meta-analysis. However, SNPs previously associated with natural HIV control linked to HLA-B (rs2395029 [p = 0.005; OR = 1.70], rs59440261 [p = 0.003; OR = 1.78]), MICA (rs112243036 [p = 0.011; OR = 1.45]), and PSORS1C1 loci (rs3815087 [p = 0.017; OR = 1.39]) showed nominal association with this phenotype. Genetic factors associated with the long-term HIV controllers without risk of immunologic progression are those previously related to the overall HIV controller phenotype.
Keywords: Virus del SIDA; Metagenome-Wide Association Study (MWAS); HIV Disease Progression; HIV Controllers; Disease Susceptibility